Discovery of Putative Herbicide Resistance Genes and Its Regulatory Network in Chickpea Using Transcriptome Sequencing - Iquebal, Mir A.; Soren, Khela R.; Gangwar, Priyanka; Shanmugavadivel, P. S.; Aravind, K.; Singla, Deepak; Jaiswal, Sarika; Jasrotia, Rahul S.; Chaturvedi, Sushil K.; Singh, Narendra P.; Varshney, Rajeev K.; Rai, Anil; et al. (Frontiers in Plant Science, 2017)
Background Chickpea (Cicer arietinum L.) contributes 75% of total pulse production. Being cheaper than animal protein, makes it important in dietary requirement of developing countries. Weed not only competes with chickpea resulting into drastic yield reduction but also creates problem of harbouring fungi, bacterial diseases and insect pests. Chemical approach having new herbicide discovery has constraint of limited lead molecule options, statutory regulations and environmental clearance. Through genetic approach, transgenic herbicide tolerant crop has given successful result but led to serious concern over ecological safety thus non-transgenic approach like marker assisted selection is desirable. Since large variability in tolerance limit of herbicide already exists in chickpea varieties, thus the genes offering herbicide tolerance can be introgressed in variety improvement programme. Transcriptome studies can discover such associated key genes with herbicide tolerance in chickpea. Results This is first transcriptomic studies of chickpea or even any legume crop using two herbicide susceptible and tolerant genotypes exposed to imidazoline (Imazethapyr). Approximately 90 million paired-end reads generated from four samples were processed and assembled into 30803 contigs using reference based assembly. We report 5759 differentially expressed genes (DEGs), of which 3037 were regulated by 980 miRNAs, 1528 transcription factors associated with 897 DEGs, 47 Hub proteins, 3540 putative Simple Sequence Repeat-Functional Domain Marker (SSR-FDM), 13778 genic Single Nucleotide Polymorphism (SNP) putative markers and 1174 Indels. Randomly selected 20 DEGs were validated using qPCR. Pathway analysis suggested that xenobiotic degradation related gene, glutathione S-transferase (GST) were only up-regulated in presence of herbicide. Down-regulation of DNA replication genes and up-regulation of abscisic acid pathway genes were observed. Study further reveals the role of cytochrome P450, xyloglucan endotransglucosylase/hydrolase, glutamate dehydrogenase, methyl crotonoyl carboxylase and of thaumatin-like genes in herbicide resistance. Conclusion Reported DEGs can be used as genomic resource for future discovery of candidate genes associated with herbicide tolerance. Reported markers can be used for future association studies in order to develop marker assisted selection (MAS) for refinement. In endeavour of chickpea variety development programme, these findings can be of immense use in improving productivity of chickpea germplasm.